Catalytic Decomposition of Airborne Ozone by MnCO3 and its Mechanism. (2nd January 2018) - Jia, Jingbo; Zhang, Pengyi
ABSTRACT: Ozone is an ubiquitous air pollutant. To develop a new kind of catalyst besides the usually used MnO2 for ozone decomposition, the sub-micrometer spherical MnCO3 was prepared via a facile co-precipitation method without additive agents at room temperature and characterized by XRD, BET, SEM, TGA, XPS and H2 -TPR. As-prepared MnCO3 showed better catalytic activity for ozone decomposition than that of α-MnO2, which is frequently studied in the literature. Amorphous MnOx was found on the MnCO3 surface, and it further formed when MnCO3 was exposed to the ozone flow. The MnOx layer is regarded as the active component in the catalytic ozone decomposition and crystalline MnCO3 serves as the support-stabilizing MnOx surface phase. Then MnCO3 powder was supported on non-woven fabrics through a simple and low-cost impregnation method. The MnCO3 -based non-woven fabrics exhibited 100% ozone conversion over 8 days at 25 °C with inlet ozone concentration 14 ppm and space velocity 42, 000 h −1 . This provides an alternative material for ozone-induced air cleaning.